Data exchange between transport models, regional economic models and impact models, specifically designed to facilitate environmental impact evaluation - Kronbak, Jacob (Proceedings from the Annual Transport Conference at Aalborg University, 2002)
This paper presents the present status of the TRIP sub-project 2.3: Integrated Traffic, Regional Economic and Impact Models. It deals with the basic layout of the MERGE (Model for Exchanging Regionalised Geographic Entities) data conflation model and shows an example of the use of the MERGE model for transferring transport data to a regional economic model.